Professional competencies to promote health in nursing and physical education undergraduate courses - Samyra Paula Lustoza Xavier; Lucas Dias Soares Machado; Maria Rosilene Cândido Moreira; Álissan Karine Lima Martins; Maria de Fátima Antero Sousa Machado (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to recognize the competencies for health promotion and their magnitude of expression in undergraduate health education based on the analysis of the pedagogical projects of the courses and from the teaching perspective. Methods: research with a mixed approach, carried out at a public university. The data collected from the pedagogical projects of the Nursing and Physical Education courses and through interviews and application of a matrix of Competencies in Health Promotion with 31 professors of the referred courses were analyzed in the light of Competencies Health Promotion. Results: all competencies investigated were recognized in the curricula and reports of nursing professors, but the possibility of changes was not identified in the pedagogical project of Physical Education, although this competency was recognized as extremely important by the professors, with a mode of 4.5. Final Considerations: the training process in the courses studied has favored the development of skills for health promotion.